Proses Pembentukan dan Makna Verba Resiprokal Bahasa Indonesia: Studi Kasus Dalam Teks Berita Surat Kabar Harian Singgalang - Cindy Arieska; Siti Ainim Liusti (Persona: Kajian Bahasa dan Sastra, 2022)
This study aims to: (1) describe the process of forming reciprocal verbs in the news text of the October 2021-March 2022 edition of the Singgalang Daily Newspaper, (2) describe the meaning of reciprocal verbs in the news text of the September 2021-August 2022 edition of the Singgalang Daily Newspaper. This research is qualitative using descriptive method. The results of this study are the process of formation and meaning of Indonesian reciprocal verbs in news texts in the October 2021-March 2022 edition of the Singgalang Daily Newspaper: first, the process of forming verbs is found through, (1) affixation, namely ber- + basic verb, ber- + basic verb. + -an, mutual me- + basic verb, mutually me- + basic verb + -an, and mutually men- + basic verb + -i; (2) reduplication, namely ber- + basic verb reduplication + -an, basic verb1 + me + basic verb2, and ber- + basic verb reduplication; (3) composition, namely mutual morpheme + basic verb and standard morpheme + basic verb. Second, the meaning of Indonesian reciprocal verbs found is the meaning of action.